Optimization and realization of SWIPT relay channel transmission rate based on rateless code - Weijia LEI; Minghao DONG (Tongxin xuebao)
The optimization of the transmission rate and implementation of the simultaneous wireless information and power transfer in a relay system were studied.In a three-node two-hop system,the decode-and-forward protocol was employed by the relay node.One transmission period was divided into two phases.The first phase was the simultaneous transmission of the information and energy from the source to the relay.The received signal at the relay node was split to two parts.One part was used for information decoding,and the other was converted into energy for information forwarding in the second phase.In the second phase,the information was forwarded according to the decode-and-forward protocol by the relay.The power splitting factor was optimized to minimize the total time of the two hops for the transmission of a certain amount of information when the durations of the two hops were unequal.Furthermore,Raptor codes were combined with different modulation modes to realize different transmission rates on the two hops for the efficient utilization of the different channel capacities in the two hops.The selection mechanism of the codeword length of Raptor codes and modulation mode was given.The simulation proves that the two hops with unequal durations can achieve a higher throughput,and the capacity of the relay channel can be efficiently used by employing Raptor codes,and an efficient and reliable transmission is realized.